Pleomorphic adenoma: Case report (Research, Society and Development, 2022)
Pleomorphic adenoma is a benign tumor, common in salivary glands, affecting both major and minor glands. When it occurs in the minor salivary glands, the palate is the main site affected. Clinically, it presents as a painless, slow-growing, encapsulated volumetric increase. In histopathological terms, this tumor is considered mixed, since it is composed of myoepithelial and epithelial cells and has its cells separated from the rest of the tissues by means of a fibrous capsule. Treatment is by surgical excision with wide margins. This article aims to report a clinical case of a patient with a pleomorphic adenoma in the minor salivary gland located on the palate. Management was presented until obtaining its definitive diagnosis, as well as the form of treatment, seeking clinical alternatives that would provide a postoperative period with less painful symptoms. After 3 months, the patient was followed up and no clinical signs of recurrence were observed until that moment. Considering that the pleomorphic adenoma can undergo malignant transformation into a former pleomorphic adenoma, it is of paramount importance that the diagnosis is properly established, the best treatment instituted and periodic observations are made.